2010
DOI: 10.1097/prs.0b013e3181d51244
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Microplates for Internal Fixation of Mandibular Fractures

Abstract: These results indicate that two-point fixation with microplates is appropriate for the internal fixation of simple, isolated mandibular fractures. Its advantages include a high adaptability to the fracture site, occlusal self-adjustment, a minimal mass effect, and a relatively strong holding power of two-point fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Bone cement has been shown to give sufficient stabilization of isolated, single fractures by fixation with just one microplate along the external oblique ridge. thus, it may be possible to maintain the stability of the fracture site using a less rigid fixation system than has been previously thought necessary (4). in our study we observed adequate stabilization of fractured fragments in the zygomatic area.…”
Section: Resultssupporting
confidence: 57%
“…Bone cement has been shown to give sufficient stabilization of isolated, single fractures by fixation with just one microplate along the external oblique ridge. thus, it may be possible to maintain the stability of the fracture site using a less rigid fixation system than has been previously thought necessary (4). in our study we observed adequate stabilization of fractured fragments in the zygomatic area.…”
Section: Resultssupporting
confidence: 57%
“…Another proposed approach to avoiding tooth root injury is to use even smaller-diameter monocortical screws found in the microplating system. Burm and Hansen 21 reported their experience using 0.55-mm-thick microplates and 1.2-mm-diameter monocortical microscrews with a 3-or 4-mm screw length in 35 patients with mandible fractures. No tooth root injuries were reported, but other notable complications were found: malocclusion, 8.5%; asymptomatic delayed union, 2.8%; and asymptomatic plate fracture, 2.8%.…”
Section: Commentmentioning
confidence: 99%
“…There are few studies that have shown the efficacy of microplate in similar fracture condition where miniplates are currently being used. [3][4][5] [ 3 _ T D $ D I F F ] The use of microplate may be considered as meaningful shift from current practice as it is less traumatic to soft tissues, cause less priosteal tissue reflection and also make use of less implant material. Thus, it is necessary to study the efficacy of such fixture plates for mandibular fractures which has less implant material (foreign body), provides optimum rigidity, and is strong enough to bear the masticatory load with un-compromised bone healing.…”
Section: Introductionmentioning
confidence: 99%